Analysis of Factors Affecting Credit Distribution to Banks Listed on The Indonesia Stock Exchange (2017-2022) - Pratiwi, Leni Nur; Yanida, Pebri; Nugrahani, Wahyu Panji (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The study aims to analyze the influence of factors that affect credit distribution by banks. The research period was conducted for 6 (six) years from 2017 to 2022. The data used are secondary data with quantitative methods. The variables used in this study are DPK, CAR, LDR, NPL, ROA as independent variables, and credit distribution as dependent variables. The population used in this study is conventional commercial banks. By using purposive sampling, the selected banks are banks listed on the IDX, and have individual financial statements at the end of the year during the study period so that 39 conventional commercial banks were selected. The analysis method used is data panel regression using the eviews 9.0 analysis tool. Based on the results of the analysis in the study, it was found that deposits and LDRs have a positive influence on credit distribution by banks. The CAR variable has a negative influence on credit distribution. NPL and ROA variables do not affect lending policy. Meanwhile, simultaneously the five variables affect credit distribution policy.